The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1063/1.3672819
|View full text |Cite
|
Sign up to set email alerts
|

Thermal dependence of the optical gain and threshold current density of GaInNAs/GaAs/AlGaAs quantum well lasers

Abstract: Articles you may be interested inThe optical gain and radiative current density of GaInNAs/GaAs/AlGaAs separate confinement heterostructure quantum well lasers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…11 Recently, much effort has been focused on exploring the GaInAsN/GaAs QW where adding small amounts of nitrogen(N) leads to favorable changes in band alignment and pushes the emission wavelength towards 1310 nm. [12][13][14] An impact of N incorporation is the deterioration of the optical properties as defect induced nonradiative recombination (NRR) increases with increasing N concentration, 15 although recent work has shown that the addition of minimal amount of N ( 0:5%) together with a post-growth annealing treatment (680 C, 10 min) in GaInAsN QW hinder from formation of N-N pairs and clusters and thus do not lead to reduction in the intrinsic gain of the active region. 16 While the NRR could be advantageous for fast saturable aborbers (SAs) and electroabsorption modulators (EAMs) as an additional carrier recombination process, 17,18 it is largely detrimental for the gain properties, with lasing threshold densities remaining relatively high.…”
mentioning
confidence: 99%
“…11 Recently, much effort has been focused on exploring the GaInAsN/GaAs QW where adding small amounts of nitrogen(N) leads to favorable changes in band alignment and pushes the emission wavelength towards 1310 nm. [12][13][14] An impact of N incorporation is the deterioration of the optical properties as defect induced nonradiative recombination (NRR) increases with increasing N concentration, 15 although recent work has shown that the addition of minimal amount of N ( 0:5%) together with a post-growth annealing treatment (680 C, 10 min) in GaInAsN QW hinder from formation of N-N pairs and clusters and thus do not lead to reduction in the intrinsic gain of the active region. 16 While the NRR could be advantageous for fast saturable aborbers (SAs) and electroabsorption modulators (EAMs) as an additional carrier recombination process, 17,18 it is largely detrimental for the gain properties, with lasing threshold densities remaining relatively high.…”
mentioning
confidence: 99%
“…The unusually strong bowing in the fundamental band gap as a function of nitrogen (N) composition has been well studied in GaN 1−x As x alloys with low N contents in accordance with the conduction band anticrossing (BAC) model, [1][2][3][4] which are potential materials for high-efficiency hybrid solar cells, 5) long-wavelength optoelectronic devices, 6) and photoanode applications in hydrogen production. 7) On the other hand, for N-rich GaNAs, [8][9][10] the structure of the valence band (VB) is explained by the hybridization of the localized arsenic (As) states with the extended VB states of the GaN matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, during the last decade, semiconductor waveguides with strong nonlinear effects, such as the silicon and chalcogenide waveguide, have attracted tremendous attention [1,2], and have been considerably investigated and demonstrated to realize compactly optoelectronic devices for wavelength conversion [3,4], optical switching [5,6], modulation [7,8], and light propagation [9,10]. Compared to the significant previous reports, the passive GaAs semiconductor waveguide has stronger third order nonlinearity and 2-photon absorption coefficients [11,12] and so it can be considered another highly nonlinear medium, and has already been investigated in wavelength conversion, optical switching, and other potential applications [13][14][15][16]. In general, it is thought that the GaAs based waveguide is strictly limited in signal processing due to its enhanced free carrier related effects.…”
Section: Introductionmentioning
confidence: 99%